2018
DOI: 10.20517/2574-1209.2018.16
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants of renin on the prevalence of diabetic nephropathy

Abstract: Aim: Renin, a component of the Renin-Angiotensin-Aldosterone System (RAAS), is produced in the juxtaglomerular cells of the kidney. It is an important factor for the regulation of blood pressure and electrolyte balance and encoded by the REN gene. Recent studies suggest that the RAAS is a regulator of kidney functions. Individuals with REN variants have been associated with high blood pressure. We substantiated the hypothesis that genetic variants of REN gene have significant association with prevalence of nep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 59 publications
(72 reference statements)
1
2
0
Order By: Relevance
“…Meta-analysis performed by Xu et al demonstrated association of allelic frequency as well as co-dominant homozygous and recessive models of inheritance with regard to −344 T/C polymorphism within promoter region of CYP11B2 gene with the increased risk of diabetic nephropathy [112]. Similar association was observed by Purkait et al [113] in Indian population. Promoter regions play important regulatory roles in gene transcription followed by formation of a functional protein through translation.…”
Section: T2dm and Raas: Contribution Of The Raas Components To The Pathogenesis Of T2dsupporting
confidence: 60%
See 1 more Smart Citation
“…Meta-analysis performed by Xu et al demonstrated association of allelic frequency as well as co-dominant homozygous and recessive models of inheritance with regard to −344 T/C polymorphism within promoter region of CYP11B2 gene with the increased risk of diabetic nephropathy [112]. Similar association was observed by Purkait et al [113] in Indian population. Promoter regions play important regulatory roles in gene transcription followed by formation of a functional protein through translation.…”
Section: T2dm and Raas: Contribution Of The Raas Components To The Pathogenesis Of T2dsupporting
confidence: 60%
“…Previous studies reported association of renin gene polymorphisms with number of non-communicable diseases including diabetic nephropathy [89], increased risk of vascular complications [90], plasma renin activity [91], susceptibility to hypertension in a variety of ethnic groups [92][93][94][95], T2D [96] with inconsistent results [97][98][99]. Few studies did not find any significant association of renin rs16853055 with diabetes and diabetic nephropathy diseases [100,101] while Purkait et al [102] found an association of this variant with diabetic nephropathy in Indian population along with strong linkage disequilibrium with rs16853055. On the other hand, Deinum et al reported weak association of renin gene polymorphism present in the first intron (involved in the regulation of transcription of renin) with diabetic nephropathy [89,103].…”
Section: T2dm and Raas: Contribution Of The Raas Components To The Pathogenesis Of T2dmentioning
confidence: 99%
“…There is a paucity of data on REN ( rs16853055 ) polymorphism. Purkait et al showed that this polymorphism had no association with diabetic nephropathy in participants of Indian ancestry [ 93 ]. Since this SNP has not yet been analysed within the realm of HDP co-morbid with HIV in sub-Saharan Africa, particularly South Africa, extensive research is required to enhance our understanding of its role as a genetic contributor to disease development as well as its associated functional properties.…”
Section: Genetic Appraisal Of Raasmentioning
confidence: 99%